The effect of advanced glycation end products on cellular signaling molecules in skeletal muscle - Tatsuro Egawa; Yoshitaka Ohno; Shingo Yokoyama; Ayumi Goto; Rika Ito; Tatsuya Hayashi; Katsumasa Goto (Japanese Society of Physical Fitness and Sports Medicine, 2018)
The accumulation of advanced glycation end products (AGEs) in the body causes the pathogenesis of aging-related diseases by inhibiting the normal properties and functions of proteins and the modulation of cellular signal transduction. Glycation stress induced by AGEs accumulation has the potential to contribute to sarcopenia: age-related reductions in muscle mass, strength, and function. However, the molecular response to AGEs in skeletal muscle is not fully understood. Therefore, to understand changes in cellular signaling in response to AGEs, this study aimed to investigate the phosphorylation status of phosphoproteins in AGEs-treated skeletal muscle. Treatment of C2C12 skeletal muscle cells with glucose-induced AGEs (0.1 mg/mL) for 5 days suppressed myotube formation, and this was accompanied by Nε-carboxymethyl-lysine accumulation. Reverse phase protein array analysis revealed that treatment with AGEs (glyoxylic-, pyruvate-, glycolaldehyde-, and glucose-induced AGEs) increased phosphorylation at eight phosphorylation sites and decreased phosphorylation at 64 phosphorylation sites. The phosphorylation level of signal transducer and activator of transcription 3 (STAT3) Tyr705 was most enhanced, and that of extracellular signal-regulated kinase (ERK) Thr202/Tyr204 was most suppressed. Almost all phosphorylation sites related to insulin/insulin-like growth factor 1 signaling were downregulated by AGEs. Increased STAT3 Tyr705 phosphorylation and decreased ERK Thr202/Tyr204 phosphorylation were observed in the skeletal muscles of mice treated with a diet high in AGEs for 16 weeks. These findings suggest that AGE accumulation impairs cellular signal transduction pathways in skeletal muscle cells, and thereby has the potential to induce skeletal muscle loss.